How Education Creates Your Wages, A Case of Manufacturing and Retail Companies in Surabaya - Kurniawan, Esther Elysia; Kristiyanto, Sony (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2024)
Education has an important role in the labor market. One component in determining the level of wages for workers is the level of education that the worker has. Apart from that, the level of education is one of the requirements for workers to be able to reach a certain level of position. The problem that then arises is how the level of education can reflect the level of wages that workers will receive, especially workers in the manufacturing and retail industries. In some cases, even though the level of education plays an important role, work experience, worker skills and the performance of the worker concerned are the keys for workers to get higher wages. This condition then gave rise to a debate regarding whether or not education was necessary in the labor market and whether it was true that the level of education would correlate with workers' wages. By using qualitative research methodology with a phenomenological paradigm, this research tries to reveal more details about this phenomenon. Manufacturing and retail companies were chosen as research subjects considering the complexity of the workers working in these companies. Manufacturing and retail companies have complex characteristics in their employment structure. Meanwhile, Surabaya was chosen because the city of Surabaya has the characteristics of an industrial and trade city in its economic structure. This research comes to the conclusion that basically education will be able to have an impact on workers' wages, but how big this impact will be will depend on the company where the worker works. A wage system that relies on bonuses or commissions based on worker performance will indirectly mean that the impact of education on wages will not be visible in real terms.